Signal functions for measuring the ability of health facilities to provide abortion services: an illustrative analysis using a health facility census in Zambia - Campbell, Oona M.R.; Aquino, Estela M. L.; Vwalika, Bellington; Gabrysch, Sabine (BMC pregnancy and childbirth, 2016)
Annually, around 44 million abortions are induced worldwide. Safe termination of pregnancy (TOP) services can reduce maternal mortality, but induced abortion is illegal or severely restricted in many countries. All abortions, particularly unsafe induced abortions, may require post-abortion care (PAC) services to treat complications and prevent future unwanted pregnancy. We used a signal-function approach to look at abortion care services and illustrated its utility with secondary data from Zambia.